Decreased seizure threshold in an eclampsia-like model induced in pregnant rats with lipopolysaccharide and pentylenetetrazol treatments. - Qian Huang; Lei Liu; Bihui Hu; Xiaodan Di; Shaun Patrick Brennecke; Huishu Liu (PLoS ONE)
Objective Eclampsia is a poorly understood but potentially fatal complication of pregnancy. Research to date on this disorder has been hampered by the lack of a suitable animal model. To correct this deficiency, this report describes the generation of a rat eclampsia-like model using pentylenetetrazol (PTZ) in a previously established rat preeclampsia model. Method Rats were administered lipopolysaccharide (1.0 µg/kg) by tail vein injection on gestational day 14 to establish preeclampsia (PE). PE and control rats (non-pregnant, NP; normal-pregnant, P) were injected intraperitoneally (i.p.) with PTZ (40 mg/kg) to induce seizures. In separate experiments, MgSO4 (270 mg/kg IP) was injected in advance of PTZ into PE rats to observe its effect on PTZ-induced seizures. Results PE conditions were verified in rats after LPS administration by significantly higher blood pressure (P<0.01) and urinary albumin excretion (P<0.05), elevated sFlt-1 (P<0.05) and decreased PlGF serum levels (P<0.05), and evidence of hepatic dysfunction compared to control groups. PTZ successfully induced seizure activity in all groups studied. Latency to seizure was significantly (P<0.01) less in the PE-PTZ group (73.2 ± 6.6 sec.) than in PTZ-treated controls (107.0 ± 7.4 sec.). Pretreatment with MgSO4 prolonged (P<0.05) latency to seizure, shortened seizure duration and decreased seizure rates. Significant increased (P<0.05) in the serum levels of the inflammatory cytokines TNF-α and IL-1β in PE and PE-PTZ groups, and decreased (P<0.05) in their levels following MgSO4 administration. Conclusion This PTZ-induced eclampsia-like rat model is comparable to the human condition of eclampsia and may serve as a useful research tool for future studies of this disease. The increased inflammatory cytokines in preeclampsia are coincident with a decreased threshold for PTZ-induced seizures, suggesting that an inflammatory mechanism may contribute to the susceptibility to seizure activity and inflammation might have an important role in eclampsia.